Serious Games for Stroke Telerehabilitation of Upper Limb - A Review for Future Research - Paula Amorim; Beatriz Sousa Santos; Paulo Dias; Samuel Silva; Henrique Martins (International Journal of Telerehabilitation)
Maintaining appropriate home rehabilitation programs after stroke, with proper adherence and remote monitoring is a challenging task.  Virtual reality (VR) - based serious games could be a strategy used in telerehabilitation (TR) to engage patients in an enjoyable and therapeutic approach. The aim of this review was to analyze the background and quality of clinical research on this matter to guide future research. The review was based on research material obtained from PubMed and Cochrane up to April 2020 using the PRISMA approach.  The use of VR serious games has shown evidence of efficacy on upper limb TR after stroke, but the evidence strength is still low due to a limited number of randomized controlled trials (RCT), a small number of participants involved, and heterogeneous samples. Although this is a promising strategy to complement conventional rehabilitation, further investigation is needed to strengthen the evidence of effectiveness and support the dissemination of the developed solutions.